Implementasi Prinsip Ekonomi Syariah dalam Manajemen Sumber Daya Manusia di Pondok Pesantren Darunnajah: Studi Deskriptif tentang Pengaruhnya terhadap Pengembangan Potensi Santri - Ulya, Mawaddatul; Hilyawati, Yusnina (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2023)
This study aims to explore the implementation of sharia economic principles in the context of human capital management at Darunnajah Islamic Boarding School and its impact on the development of santri potential. This research is a descriptive study that uses a qualitative approach through in-depth interviews, observations, and document analysis to understand how sharia economic principles are applied in human resource management at the pesantren. The approach based on Islamic values, such as justice, togetherness, and transparency is reflected in the policies of recruitment, training, development, and compensation for students. The active participation of pesantren leaders in empowering santri through sharia programs has affected the growth of their individual potential. In this context, the implementation of sharia economic principles has contributed positively to the development of santri potential. They not only develop relevant economic skills, but also gain a deeper understanding of the ethical and moral values underlying economic activities. The implications of these findings highlight the importance of the integration of Islamic economic values in human resource management in Islamic boarding schools to facilitate the holistic development of santri.